Predictors of decline in IADL functioning among older survivors following the Great East Japan earthquake: A prospective study. (March 2017) - Tsuboya, Toru; Aida, Jun; Hikichi, Hiroyuki; Subramanian, S.V.; Kondo, Katsunori; Osaka, Ken; Kawachi, Ichiro
Abstract: Introduction: We described associations between the type of disaster experience and change in instrumental activities of daily living among older adult survivors before-after a terrible disaster. Methods: The study took advantage of a "natural experiment" afforded by the Japan Gerontological Evaluation Study (JAGES), a nationwide cohort study established in 2010, seven months prior to the earthquake and tsunami. A follow-up survey was conducted in 2013. This study was conducted in Iwanuma, which was directly struck by tsunami. Our sample comprised community-dwelling aged survivors in Iwanuma who responded to questions about personal circumstances and functional status both before and after the disaster (N = 3547). Personal experiences of earthquake and tsunami damage was used as an exposure variable. The outcome was changes in self-reported 13-item instrumental activities of daily living (IADL), which was assessed both before and after the disaster. Results: Among the participants, 931 reported losing family member(s) to the disaster, while a further 549 reported losing friend(s). More than half of the participants reported any damage to their houses while approximately 1 in 8 lost their car(s). The multivariable OLS regression revealed that complete house loss and disruption of internal medicine were associated with significantly worse IADL: −0.67 points (95%CI: −0.99, −0.34) for entirely destroyed homes; −0.40 points (95% CI: −0.71, −0.092) for disruption of internal medicine. By contrast, loss of family/friends/pets/cars and disruption to the other medical service were not associated with decline in IADL. Conclusion: Complete house loss and disruption of access to internal medicine after a disaster were associated with significant adverse impact on decline in physical and cognitive functions 2.5 years after the disaster, while loss of family/friends was not. Highlights: Few studies have examined physical and cognitive function after natural disasters. House damage seemed to result in a more lasting adverse impact on physical health. Accessing to internal medicine was associated physical and cognitive function. Loss of loved ones was not associated with physical and cognitive functions. Monitoring of survivors is needed even up to 3 years after natural disasters.